Informative celebrations of a proclaimed death: the death of Hugo Chávez in the main Brazilian weekly magazines - Brandão Tavares, Frederico (2016)
This paper is a reflection on the coverage of the death of former Venezuelan President Hugo Chávez in the four major Brazilian weekly magazines devoted to news (CartaCapital, Época, IstoÉ and Veja). The study intends to think over media trends and their marks in a broader communication context, considering how such an event has been approached by the above-mentioned printed media, instead of problematizing on the coverage about the death of Hugo Chávez. The intention is to observe the composite built by Brazilian newsmagazines related to a great event and at the same time to explain how such magazines are constantly “happenning” due to their practices. Thus, they have a particular behavior when covering public people deaths.